A novel lidar system for profiling the aerosol hygroscopic growth factor. (February 2021) - Wang, Qiang; Mao, Jiandong; Zhao, Hu; Sheng, Hongjiang; Zhou, Chunyan; Gong, Xin; Rao, Zhimin; Zhang, Yi
Highlights: A Raman lidar system is designed to detect the aerosol hygroscopic growth factor. The temperature and humidity profiles are obtained directly by the lidar system. The lidar system has important significance in studying the aerosol properties. Abstract: The scattering growth factor is an important parameter for description of aerosol hygroscopic growth properties. In this work, a multi-wavelength polarized Raman lidar system is designed that detects the hygroscopic characteristics of aerosol particles. The principle of the aerosol hygroscopic growth factor retrieval method is described in detail. To verify the feasibility of this lidar system, numerical simulations are performed. In the simulations, a 532 nm laser with energy of 440 mJ and a 10 Hz pulse repetition rate is used as the source, a 400-mm-diameter Cassegrain reflecting telescope collects the backscattered return signals, and the 1976 US standard model with a Mie scattering profile from practical observations is used to simulate the atmospheric environment. The results show that the lidar system is able to detect the aerosol hygroscopic growth factor profiles.